Compact optical integration instrument to measure intraocular straylight - Ginis, Harilaos (Biomed Opt Express, 2014)
Optical measurement of straylight in the human eye is a challenging task. Issues such as illumination geometry, detector sensitivity and dynamic range as well as various inherent artifacts must be addressed. We developed a novel instrument based on the principle of double-pass optical integration adapted for fast measurements in a clinical setting. The experimental setup was validated using four different diffusers introduced in front of the eyes of ten subjects. Measurement limitations and future implications of rapid optical measurement of straylight in ophthalmic diagnosis are discussed.